Effects of anthropogenic habitat disturbance and Giardia duodenalis infection on a sentinel species' gut bacteria - Kuthyar, Sahana (2021)
Habitat disturbance, a common consequence of anthropogenic land use practices, creates human–animal interfaces where humans, wildlife, and domestic species can interact. These altered habitats can influence host–microbe dynamics, leading to potential downstream effects on host physiology and health. Here, we explored the effect of ecological overlap with humans and domestic species and infection with the protozoan parasite Giardia duodenalis on the bacteria of black and gold howler monkeys (Alouatta caraya), a key sentinel species, in northeastern Argentina. Fecal samples were screened for Giardia duodenalis infection using a nested PCR reaction, and the gut bacterial community was characterized using 16S rRNA gene amplicon sequencing. Habitat type was correlated with variation in A. caraya gut bacterial community composition but did not affect gut bacterial diversity. Giardia presence did not have a universal effect on A. caraya gut bacteria across habitats, perhaps due to the high infection prevalence across all habitats. However, some bacterial taxa were found to vary with Giardia infection. While A. caraya's behavioral plasticity and dietary flexibility allow them to exploit a range of habitat conditions, habitats are generally becoming more anthropogenically disturbed and, thus, less hospitable. Alterations in gut bacterial community dynamics are one possible indicator of negative health outcomes for A. caraya in these environments, since changes in host–microbe relationships due to stressors from habitat disturbance may lead to negative repercussions for host health. These dynamics are likely relevant for understanding organism responses to environmental change in other mammals.